Measles in Kirkuk Governorate: Cohort Study - Abdul Sahib, sanaa; Mahmud, nazar (Iraqi National Journal of Nursing Specialties, 2011)
Objective(s): To describe the demographic attributes, vaccination status of measles patients and the occurrence of the disease according to time and place in Kirkuk governorate during the year 2010. Methodology: The epidemiological study (a descriptive study) on measles cases was carried out in Kirkuk province which is one of the Iraqi governorates from January 20th to July 30th, 2011. Data were collected retrospectively by review of patients’ files that were registered at the department of statistic in health directorate of Kirkuk during the year 2010. A purposive "non-probability" sample of (152) confirmed measles cases (clinically and laboratory) that were registered at the department of statistic in health directorate of Kirkuk during the year 2010, were selected for the purpose of the study. These data include demographic data, vaccination status, place and time of reporting the cases by month. The obtained data of the registered cases were entered in to the computer and analyzed through the use of the statistical package social sciences (SPSS 11.5); the data analysis was preformed through descriptive statistical approach, such as (frequency and percentage). Results: The study findings revealed that (49.3%) of measles cases were more than fifteenth years of age, (57.9%) of them were male. Up to half of cases occurred inside Kirkuk city, and according to vaccination status, (47.4%) of measles cases were vaccinated. Recommendations: The study highlighted the necessity of timely measles vaccine campaign, additional dose of vaccine to include also adolescents and adults who may be sensitive to measles, and importance of health education for unimmunized adult person.